Development of the Leptospirosis Surveillance System in Manang District, Satun Province: Oranuch Nararak - Nararak, Oranuch; Paduka, Nusaree; Ditsuwan, Thanittha (Princess of Naradhiwas University Journal, 2024)
The purpose of this study was to create a surveillance system for leptospirosis. The process was conducted from January to July of 2023 in Manang district, Satun Province. Three steps were involved in this action research: 1) Research the state of situation and barriers to leptospirosis surveillance, prevention, and control; 2) Create a surveillance system; and 3) Assess the system's efficacy. The instrument utilized in this study was an application included Google form and Google sheet. Data analysis used in this study were number, and percentage. According to the findings, the developed application had an easily legible report, easily accessible information that could be shared and accessed on a website, and a real time report. The developed application facilitated quick access to plan for disease surveillance, control, and prevention. Health care providers, volunteers, and stakeholders all acknowledged high levels of satisfaction and benefit from the developed system. According to the surveillance system's results, 31 patients had leptospirosis. Twenty-eight patients met the criteria of the surveillance system, whereas twenty-seven patients met the definition and report of the 506 protocols. The sensitivity of surveillance system was 96.42 and positive predictive value was 90.32. The completeness and accuracy of data were in the good level. Timeliness was 77.77%. The plan for disease prevention can be enhanced using this surveillance system by sharing data with relevant organizations. As a result, this surveillance system ought to be expanded to include additional districts for the purpose of surveillance and preventing leptospirosis.